Convergence Model of Governance: A Case Study of the Local Government System of Pakistan (The Pakistan Development Review, 2006)
The future of devolution plan in Pakistan may be analysed in view of our Convergence model. This model views stability of the local Govt. system drawn on Devolution Plan 2001. It claims that as there would be more volatile and non-committed (floating) number of agents in the political market and governance system, there is more probability of divergence; i.e. the system will remain unstable. Contrary to that more is the systematic trend in political market and governance system more is the probability that the convergence in the system occurs and that in turn leads to stability of the over all system. In this ‘Convergence’ Model different types of agents have been highlighted on the basis of their political affiliation and being in competition as ruling elite and/or their allies and non-ruling elite and/or their allies.